The ResQu Index: A new instrument to appraise the quality of research on birth place. - Saraswathi Vedam; Chris Rossiter; Caroline S E Homer; Kathrin Stoll; Vanessa L Scarf (PLoS ONE)
Objective Place of birth is a known determinant of health care outcomes, interventions and costs. Many studies have examined the maternal and perinatal outcomes when women plan to give birth in hospitals compared with births in birth centres or at home. However, these studies vary substantially in rigour; assessing their quality is challenging. Existing research appraisal tools do not always capture important elements of study design that are critical when comparing outcomes by planned place of birth. To address this deficiency, we aimed to develop a reliable instrument to rate the quality of primary research on maternal and newborn outcomes by place of birth. Study design The instrument development process involved five phases: 1) generation of items and a weighted scoring system; 2) content validation via a quantitative survey and a modified Delphi process with an international, multi-disciplinary panel of experts; 3) inter-rater consistency; 4) alignment with established research appraisal tools; and 5) pilot-testing of instrument usability. Results A Birth Place Research Quality Index (ResQu Index) was developed comprising 27 scored items that are summed to generate a weighted composite score out of 100 for studies comparing planned place of birth. Scale content validation indices were .89 for clarity, .94 for relevance and .90 for importance. The Index demonstrated substantial inter-rater consistency; pilot-testing confirmed feasibility and user-friendliness. Conclusion The ResQu Index is a reliable instrument to evaluate the quality of design, methods and interpretation of reported outcomes from research about place of birth. Higher-scoring studies have greater potential to inform evidence-based selection of birth place by clinicians, policy makers, and women and their families. The Index can also guide the design of future research on place of birth.